Reduced Global-Brain Functional Connectivity of the Cerebello-Thalamo-Cortical Network in Patients With Dry Eye Disease - Pan, Pan; Wei, Shubao; Ou, Yangpan; Liu, Feng; Li, Huabing; Jiang, Wenyan; Li, Wenmei; Lei, Yiwu; Guo, Wenbin; Luo, Shuguang (Frontiers in Human Neuroscience, 2020)
Background: The pathophysiology of patients with dry eye disease (DED) is associated with abnormal functional connectivity (FC). The present study aims to probe alterations of voxel-wise brain-wide FC in patient with DED at rest in an unbiased way. Method: A total of 20 patients with DED and 23 controls matched by age, sex and years of education underwent resting-state functional magnetic resonance imaging scans. Global-brain FC (GFC) was adopted to analyze the images. Support vector machine (SVM) was utilized to differentiate the patients from the controls. Results: Compared with the controls, patients with DED exhibited decreased GFC in the right cerebellum lobule Ⅷ/inferior semi-lunar lobule and left thalamus that belonged to the cerebello-thalamo-cortical network. The GFC values in the left thalamus of the patient were positively correlated to the illness duration (r=0.589, p=0.006). Decreased GFC values in the left thalamus could be used to discriminate the patients from the controls with optimal accuracy, sensitivity and specificity (88.37%, 85.00% and 91.30%) Conclusions: Our findings indicate that decreased GFC in the brain regions associated with cerebello-thalamo-cortical network may provide a new insight for understanding the pathological changes of FC in DED. GFC values in the left thalamus may be utilized as a potential biomarker to identify the patients from the controls.